Hygiena Study: audit of women managed with Cone Biopsy at Groote Schuur Hospital from 1st April 2013 to 31st October 2015 - Kadwa, Khatija (Department of Obstetrics and Gynaecology, 2017)
INTRODUCTION: Cervical cancer is the second commonest cancer in South Africa and the commonest amongst Black females with a Lifetime Risk (LR) of 1:35. In South Africa the problem has been compounded by the HIV epidemic as well as a lack of resources and infrastructure to offer an adequate screening and treatment programme. Cone biopsies are one of the diagnostic and sometimes therapeutic modalities used to assess and treat cervical precursors and cervical cancer. Unfortunately, cone biopsy of the cervix remains a morbid procedure often performed on young women in the reproductive age group and has resultant complications. OBJECTIVE: To audit the demographics, indications, histology and post cone management and outcome of women requiring cone biopsies of the cervix, at Groote Schuur Hospital Colposcopy Clinic between 1st April 2010 and 31st October 2013. METHODS: A group of women attending the colposcopy clinic, and requiring cone biopsies between 1st April 2010 and 31st October 2013 were identified from a computerized database, known as the Hygiena Database. Women who had an incomplete dataset were excluded. Folder review and review of the National Health Laboratory Services was also conducted. Patient demographics, indications, cone histology and follow up at 4-6 months, 10-12 months and > 12 months were analysed. Age, parity, HIV status, CD4 count, ARV status and cone margin involvement were included in the univariate and multivariate analysis to determine predictors of persistent disease RESULTS: Three hundred and seventy six cone biopsies were performed during the study period, with a mean age of 42.3 years, mean parity of 2. The majority of women [56,7% (213/376)] were HIV positive. The final histology indicated that 65,2% (246/376) of the women had high-grade disease (CIN 2/3 or HSIL) and 12,5% (47/376) had microinvasion. Ectocervical margins were clear in 57,6% (212/368) of cases and endocervical margins were clear in 54,6% (201/368) of specimens. Fifty-one cancers were detected during the study period. In the multivariate analysis age 40-49yrs (RR 1.4, 95% CI 1.01-2.0: p=0,043), ectocervical margin involvement with CIN 2/3 (RR 1.8, 95% CI 1.1-3.0: p-0.017) and endocervical margin involvement with CIN 2/3 (RR 1.5, 95% CI 1.04-2.3; p=0,031) and microinvasion ( RR 2.4, 95% CI 1.4-4.3; p=0.003) were all predictors of persistent disease. CONCLUSION: The use of cone biopsy is a valid diagnostic and sometimes therapeutic procedure at Groote Schuur Hospital with significant detection of high grade disease and cervical cancer. Women aged 40-49 years and positive cone margins are strong predictors of persistent disease. Improved compliance and a reduction in positive margins are two areas that need to be addressed to improve the current treatment programme. Use of cone biopsy as surgical therapy for early stage cancer appears promising but needs further study.